GE_GERICHTE C/14887/2018 vom 9. April 2019 - GE Cour de justice (2019)
MAINLEVÉE DÉFINITIVE;COMPENSATION DE CRÉANCES;ABUS DE DROIT | LP.80; LP.81.al1; CO.128.al2; CO.134.al1.ch1; CO.120.al1; CO.125.al2; CC.2.al2